1995
DOI: 10.1515/dmdi.1995.12.3-4.207
|View full text |Cite
|
Sign up to set email alerts
|

Functional and DNA Sequence Divergence of the CYP71 Gene Family in Higher Plants

Abstract: During ripening of avocado (Persea americana), the CYP71A1 mRNA and protein accumulate to relatively high levels. Although the CYP71A1 gene was the first plant P450 to be cloned and sequenced, the functional role of this P450 remains obscure. Substrate studies have shown that CYP71A1 will metabolize various monoterpenes (nerol and geraniol), although these have not been detected in ripening fruit. Using DNA from a conserved domain of the CYP71A1 gene, we have explored the scope of the CYP71 (or related) gene f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The CYP81A6 sequence also showed similarity to the other hydroxylase proteins (Fig. 2E) such as CYP71A1 (Christoffersen et al 1995), CYP75B1/B2 (Brugliera et al 1999;Rupasinghe et al 2003), CYP76A1/B6 Collu et al 2001), CYP82A1/B1 proteins. According to the nomenclature for the P450 superfamily (http://drnelson.utmem.edu/CytochromeP450.…”
Section: Fine Mapping Of Belmentioning
confidence: 71%
“…The CYP81A6 sequence also showed similarity to the other hydroxylase proteins (Fig. 2E) such as CYP71A1 (Christoffersen et al 1995), CYP75B1/B2 (Brugliera et al 1999;Rupasinghe et al 2003), CYP76A1/B6 Collu et al 2001), CYP82A1/B1 proteins. According to the nomenclature for the P450 superfamily (http://drnelson.utmem.edu/CytochromeP450.…”
Section: Fine Mapping Of Belmentioning
confidence: 71%
“…This homology is of special interest since CYP82A1 is a wound-inducible P450 from pea, a legume with a wound-or defense-related secondary metabolism similar to soybean. Three cDNAs, CYP71A9, CYP71D8 and CYP71D9, belong to the CYP71 family, which seems to play a variety of functional roles, among them terpenoid metabolism (Christoersen et al 1995). Because of this divergence, clues as to its biochemical functions are lacking.…”
Section: Isolation Of Full-length Cdnasmentioning
confidence: 99%
“…As each CYP catalyses a different reaction, it is unlikely that all CYPs play a role in the diterpene glycoside synthesis. Four CYP families, from which seven members were found in the QTL region as defined by Maharijaya et al ( 2015 ), were previously suggested to play a role in terpenoid metabolism (Christoffersen Rolf et al 1995 ; Schopfer and Ebel 1998 ; Ro et al 2005 ; Ohnishi et al 2006 ; Thornton et al 2010 ; Höfer et al 2013 ). The CYP89 and CYP94 families, from which eight members were found in the QTL region, do not seem to play a role in the terpenoid pathway (Kahn et al 2001 ; Christ et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%